Orientation-dependent micromechanical behavior of nacre: In situ TEM experiments and finite element simulations. (15th July 2022) - Peng, Xiang-Long; Lee, Subin; Wilmers, Jana; Oh, Sang Ho; Bargmann, Swantje
Abstract: Nacre's superior mechanical properties and failure behavior are strongly orientation-dependent due to its brick-and-mortar microstructure. In this work, the anisotropic microscopic deformation and the resulting macroscopic mechanical properties are evaluated under different loading conditions. Our in situ transmission electron microscopy deformation experiments and finite element simulations reveal that nacre possesses enhanced indentation resistance along the direction normal to the tablets through delocalization of indentation-induced deformation by taking advantage of its layered structure. In addition, nacre's ability to recover from large deformations is observed. We study the strong loading direction dependence of nacre's macroscopic mechanical properties and elucidate the underlying microscopic deformation patterns in the tablets and the soft matrix. Particularly, its performance along the transverse direction is optimized to withstand the loading conditions in nature. We show the importance of the vertical matrix for the initial stiffness and fracture toughness of the composite. These findings provide guidelines for designing nacre-inspired artificial composites with enhanced mechanical properties. Statement of significance: Nacre is widely recognized as an excellent structural model for designing bio-inspired tough and strong artificial composites. Due to its brick-and-mortar microstructure, it exhibits loading direction-dependent mechanical behavior. In this contribution, we investigate the macroscopic mechanical properties and microscopic deformation behavior of nacre under different loading conditions by means of in situ TEM deformation tests and FE simulations. It is found that effective elastic moduli and microscopic deformation strongly depend on the loading direction. The organic matrix is highly deformable. The indentation resistance along the direction normal to tablets is enhanced via deformation delocalization. Our quantitative and qualitative results provide guidelines on optimizing the mechanical properties of nacre-inspired novel composites. Graphical abstract: Image, graphical abstract